Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1021/acsami.7b01985
|View full text |Cite
|
Sign up to set email alerts
|

Camera Method for Monitoring a Mechanochromic Luminescent β-Diketone Dye with Rapid Recovery

Abstract: Mechanochromic luminescent (ML) materials, which show a change in emission due to an applied mechanical stimulus, are useful components in a variety of applications, including organic light-emitting diodes, force sensors, optical memory storage, and next-generation lighting materials. While there are many different ML active derivatives, few show room temperature self-erasing. Thin films of the methoxy substituted β-diketone, gbmOMe, initially exhibited blue (428 nm) emission; however, green (478 nm) emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 49 publications
3
33
0
Order By: Relevance
“…The 5 % dye loading spectrum of 1 has a second broader peak at around 470 nm, possibly due to aggregation effects caused by increased dye‐dye interactions. Interestingly, 3 did not show the usual trend of red‐shifted emission with higher dye loading, possibly due to steric effects of the closely positioned methoxy substituents preventing π‐stacking . The fluorescence maxima for all three dye loadings for 3 resided around 440 nm.…”
Section: Figurementioning
confidence: 94%
See 1 more Smart Citation
“…The 5 % dye loading spectrum of 1 has a second broader peak at around 470 nm, possibly due to aggregation effects caused by increased dye‐dye interactions. Interestingly, 3 did not show the usual trend of red‐shifted emission with higher dye loading, possibly due to steric effects of the closely positioned methoxy substituents preventing π‐stacking . The fluorescence maxima for all three dye loadings for 3 resided around 440 nm.…”
Section: Figurementioning
confidence: 94%
“…Interestingly, 3 did not show the usual trend of red-shifted emission with higher dye loading, possibly due to steric effects of the closely positioned methoxy substituents preventing p-stacking. [53] The fluorescence maxima for all three dye loadings for 3 resided around 440 nm.…”
mentioning
confidence: 94%
“…In 2017, Fraser and coworkers developed a camera method to investigate the self-recovering MCL behavior of thin films prepared from crystalline β-diketone dye 12 (Figure 3f ). 27 The rapid self-recovering process of the thin film was analyzed by the intensity decay of each pixel observed by a video camera. This study revealed the importance of film thickness for selfrecovering MCL as significant fluctuations in recovery behavior were observed for thinnest films.…”
Section: Organic Crystalline Compounds With Various MCL Propertiesmentioning
confidence: 99%
“…On the other hand, tetracoordinated organoboron complexes are intensively investigated as highly emissive luminophores. A large number of O,O-coordinated organoboron complexes based on β-diketone ligands, [13] and N,O-coordinated analogues, based on β-ketoiminate or β-iminoenolate ligands, [14] were studied as promising MFC materials. Nevertheless, despite the great progress, the obtaining of MFC-active organoboron complexes, exhibiting high solid-state photoluminescence quantum yield (PLQY), still remains challenging.…”
Section: Introductionmentioning
confidence: 99%